The Rules of Medical Experimentation on People in the Light of the Polish Law and Administrative Solutions - Kulikowska-Kulesza, Justyna; Kościuk, Dominik (Public Governance, Administration and Finances Law Review, 2021)
In the history of mankind there are known cases of conducting experiments with a goal against people. After all, there has been eugenic research, or research leading to the creation of biological weapons. Such experiments are usually hidden from the public and governed by the internal and classified regulations of particular states. That is why it is important for the domestic legal orders world-wide to establish not only research methods and ways of conducting experiments (from the point of view of medical art and effectiveness of research) but also – and perhaps even more importantly – legal principles and rules limiting the conduct of medical experiments, and to establish rules of conduct with the effect of saving and prolonging the life and health of the patient. This article will analyse the Polish legal regulations and Polish doctrine in the field as a case study, describing an example of the national measures implemented to provide control of the research and medical experiment procedures.